89.0k views
3 votes
Let h(x)=20e^kx where k ɛ R (Picture attached. Thank you so much!)

Let h(x)=20e^kx where k ɛ R (Picture attached. Thank you so much!)-example-1
User ZooZ
by
5.5k points

1 Answer

5 votes

Answer:

A)


k=0

B)


\displaystyle \begin{aligned} 2k + 1& = 2\ln 20 + 1 \\ &\approx 2.3863\end{aligned}

C)


\displaystyle \begin{aligned} k - 3&= \ln (1)/(2) - 3 \\ &\approx-3.6931 \end{aligned}

Explanation:

We are given the function:


\displaystyle h(x) = 20e^(kx) \text{ where } k \in \mathbb{R}

A)

Given that h(1) = 20, we want to find k.

h(1) = 20 means that h(x) = 20 when x = 1. Substitute:


\displaystyle (20) = 20e^(k(1))

Simplify:


1= e^k

Anything raised to zero (except for zero) is one. Therefore:


k=0

B)

Given that h(1) = 40, we want to find 2k + 1.

Likewise, this means that h(x) = 40 when x = 1. Substitute:


\displaystyle (40) = 20e^(k(1))

Simplify:


\displaystyle 2 = e^(k)

We can take the natural log of both sides:


\displaystyle \ln 2 = \underbrace{k\ln e}_(\ln a^b = b\ln a)

By definition, ln(e) = 1. Hence:


\displaystyle k = \ln 2

Therefore:


2k+1 = 2\ln 2+ 1 \approx 2.3863

C)

Given that h(1) = 10, we want to find k - 3.

Again, this meas that h(x) = 10 when x = 1. Substitute:


\displaystyle (10) = 20e^(k(1))

Simplfy:


\displaystyle (1)/(2) = e^k

Take the natural log of both sides:


\displaystyle \ln (1)/(2) = k\ln e

Therefore:


\displaystyle k = \ln (1)/(2)

Therefore:


\displaystyle k - 3 = \ln(1)/(2) - 3\approx-3.6931

User Tania Marinova
by
5.4k points